RESUMING THE "SKILLED WORKER" IDENTITY: The Filipinas' Strategies in Labor Market Participation in Melbourne, Australia. - Limpangog, Cirila P. (Kritika Kultura, 2016)
Through the lens of culture intersecting with gender, race and class, this monograph looks at the reconfiguration of skilled worker identity of 20 Philippines-born women who have immigrated to Australia. Through interviews and analyses of their lived experiences, it attempts to comprehend the complexity of their unemployment, from their encounter with the labor market, to their attempts in breaking into the workforce. It contextualizes the institutional disadvantages and discrimination befalling migrant women of non-English speaking background, as well as housework and mothering responsibilities they continue to resist at home. The complex interaction of the women's higher education, English language proficiency, their sense of purpose and other personal resources--all assisted in reframing their subordinated identity, and recapturing their careers. The women risked taking jobs lower than their qualifications, took further studies, went through rigorous accreditation, and acquired local experience, as stepping stones to regain their professions and subsequently their middle-class status. Their journey, however, is not without severe difficulties. By using agency and privilege, this monograph argues that the women epitomized the classical modernist ideology of the self within a capitalist system. They were aware of structural disadvantages and discriminatory practices, but they found ways of working within these limitations, which results to masking the hardships they endured. The study debunks the effectiveness of the notion that individual's capacity over the state "to enterprise themselves" is a success strategy.